Electronic health record to predict a heart attack used data mining with Naïve Bayes method - Johanes Fernandes Andry; Fabio Mangatas Silaen; Hendy Tannady; Kevin Hadi Saputra (International Journal of Informatics and Communication Technology (IJ-ICT), 2021)
A heart attack is a medical emergency. A heart attack usually occurs when a blood clot blocks the flow of blood to the heart. Cardiovascular disease is a variety of diseases that attack the body's cardiovascular system including the heart and blood vessels. Cardiovascular diseases (CVD) include angina, arrhythmia, heart attack, heart failure, atherosclerosis, stroke, and so on. To resolving (CVD) is to evaluate large scores of datasets, to compare for any information that can be used to forecast, to take care of organize. The method used Naïve Bayes classification because that method can determine target which can be used to answer some questions like whether the patient has the potential for heart disease. After data analyst, authors can use data to electronic health records (EHR).